Preharvest zinc sulfate spray improves the storability of longan (Dimocarpus longan Lour.) fruits by protecting the cell wall components and antioxidants of pericarp. (24th September 2018) - Luo, Tao; Niu, Jiajia; Guo, Xiaomeng; Wu, Huitao; Han, Dongmei; Shuai, Liang; Wu, Zhenxian
Abstract: BACKGROUND: Zinc (Zn) fertilization has been reported to improve the quality and storability of many fruits, but the mechanism had not been systematically studied. In this study, the effect of preharvest 0.2% zinc sulfate (ZnSO4 ) spray on the storability of longan fruits was investigated. RESULTS: The preharvest ZnSO4 spray did not significantly influence the quality but increased the Zn content in longan pericarp by 12.5‐fold. More importantly, the treatment significantly reduced the rotting rate, pericarp browning, and aril breakdown of longan fruits stored at room temperature and low temperature. Physiological and biochemical results indicated that the treatment resulted in higher water retention capacity and inhibited the degradation of cellulose, pectin, flavonoid, and phenolics of longan pericarp at the late stages of storage. Consistent with these results, the activity of cellulase, polygalacturonase, polyphenol oxidase, and lipoxygenase was significantly inhibited in the ZnSO4 ‐treated longan pericarp at the late stages of storage. CONCLUSION: Higher Zn content in the ZnSO4 ‐treated longan pericarp might help to enhance the resistance against microbial infection, inhibit the hydrolysis of cell wall components, and thus effectively protected the cell wall components, maintained the cellular compartmentation, and prevented the phenolics and flavonoid from degradation by browning‐related enzymes. © 2018 Society of Chemical Industry